(untitled) (Archives of Mechanics - Test, 1997)
The work presents results of calculations of the transverse Stokes flow through a square array of cylinders. The new functional basis has been derived and the solution is sought in the form of series expansions in this basis, the terms of which are given explicitly as functions of the volume fraction φ. The presented method enabled us to evaluate the expression for the drag force of high accuracy using symbolic computations.